Strengthening Sharia Compliance in Indonesian Sharia Cooperatives: A Governance-Based Perspective from Islamic Economic Law - Melhadi Melhadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines Sharia compliance in Indonesian Sharia cooperatives from the perspective of Sharia economic law, emphasizing the role of the Sharia Supervisory Board (DPS) in ensuring adherence to Islamic principles. While previous studies have focused on operational and financial aspects, limited attention has been given to Sharia economic law as a framework for evaluating compliance. This normative legal research employs statute and conceptual approaches through qualitative analysis of primary and secondary legal materials. The findings indicate that Indonesia has established a comprehensive regulatory framework for Sharia cooperatives. However, challenges persist, including inconsistent implementation of Sharia contracts (akad), limited effectiveness of the Sharia Supervisory Board, and inadequate understanding of Sharia economic law among cooperative managers. These weaknesses may undermine contract validity, institutional legitimacy, and member confidence. This study highlights the importance of strengthening Sharia governance by promoting substantive, rather than merely formal, compliance and provides practical recommendations for enhancing supervisory mechanisms and the sustainability of Sharia cooperatives in Indonesia